Regional Epidemiological Study on the Dental Status of the First Permanent Molar in Romanian Schoolchildren - Liana Beresescu; Gabriela Felicia Beresescu; Daniela Esian; Alexandru Vlasa; Csilla Benedek; Raluca Sabau; Alexandra Mihaela Stoica (Dentistry Journal)
Background/Objectives: Dental caries remains a significant public health challenge in Romania, with recent studies reporting a prevalence of 40% in children’s permanent teeth, with 90% of cases untreated. This study aimed to evaluate the dental status of the first permanent molars in children aged 11–12 years. Methods: This cross-sectional study was conducted over 12 months at the Integrated Center for Dental Medicine in Târgu Mureș and two private clinics in Transylvania. A total of 516 children, aged 11–12 years, were examined using the ICDAS II classification. Data on carious lesions and dental treatments performed were collected. Results: Of the 2064 first permanent molars examined, 57.99% had carious lesions, fillings, or extractions, while 41.28% were free from caries. Among the affected molars, 41.71% had untreated caries, 9.30% were filled, and 6.25% were sealed. Boys showed a significantly higher prevalence of advanced lesions (ICDAS 4–6) compared to girls. Caries predominantly affected the pits and fissures (87.46%). Conclusions: This study reveals a high prevalence of carious lesions in first permanent molars and a low rate of treatment. The findings emphasize the need for improved oral health education, increased access to dental care, and the development of national strategies to prevent and treat dental caries in children.